Symbolist Drama and New Genesis: The Concept of the Suffering Demon As the Ordering Principle of Chaos - Kobialka, Michal (Journal of Dramatic Theory and Criticism, 1988)
Symbolist Drama and New Genesis: The Concept of the Suffering Demon As the Ordering Principle of Chaos